2011
DOI: 10.1175/2011jas3661.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Evolution of North Atlantic Ridges and Poleward Jet Stream Displacements

Abstract: The development of a particular wintertime atmospheric circulation regime over the North Atlantic, comprising a northward shift of the North Atlantic eddy-driven jet stream and an associated strong and persistent ridge in the subtropics, is investigated. Several different methods of analysis are combined to describe the temporal evolution of the events and relate it to shifts in the phase of the North Atlantic Oscillation and East Atlantic pattern. First, the authors identify a close relationship between north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 45 publications
10
42
0
Order By: Relevance
“…Vilibić and Šepić (2010) found that the associated mean SLV amplitudes were approximately 70% larger at the northern tide gauges (Rovinj) than at the southern gauges (Ceuta). A similar ratio was found in our results, which we attribute to a peaking of planetary-scale dynamics over the mid-latitudes and its decrease towards the equator (Madden, 1979;Lindzen et al, 1984;Woollings et al, 2011). This hemispheric gradient in dynamics induces variations in surface air pressure and winds over the same period.…”
Section: Present Climate Slvsupporting
confidence: 91%
“…Vilibić and Šepić (2010) found that the associated mean SLV amplitudes were approximately 70% larger at the northern tide gauges (Rovinj) than at the southern gauges (Ceuta). A similar ratio was found in our results, which we attribute to a peaking of planetary-scale dynamics over the mid-latitudes and its decrease towards the equator (Madden, 1979;Lindzen et al, 1984;Woollings et al, 2011). This hemispheric gradient in dynamics induces variations in surface air pressure and winds over the same period.…”
Section: Present Climate Slvsupporting
confidence: 91%
“…The value of the LW index may reflect the presence or absence of European blocking events because the calculation region of this index includes the longitudes from 308W to 308E where Euro-Atlantic blocking events are most frequently prevalent (Shabbar et al 2001). When a blocking event follows an NAO 1 event and is situated in the Atlantic basin, an NAO 1 to NAO 2 transition event can be detected with the PC index (Luo et al 2012a,b) because NAO 2 events correspond to the presence of blocking events over the North Atlantic or Greenland (Woollings et al 2008). However, when blocking events remain over the European continent, it is difficult to observe such an NAO 1 to NAO 2 transition event in the PC index.…”
Section: Methodsmentioning
confidence: 99%
“…Although many indices have been proposed to identify NAO events, in this paper, using a region-averaged NAO index defined by Li and Wang (2003), we show that there is a link between the extreme cold weather event over Europe in January-February 2012 and the transition from a NAO 1 event to a long-lasting blocking event over the eastern Atlantic and western Europe. Because NAO 2 events correspond to blocking events over Greenland and the North Atlantic (Luo et al 2007;Woollings et al 2008;Davini et al 2012), it is reasonable to define blocking events over the North Atlantic and eastern Atlantic-European continent as the negative phase western NAO (WNAO 2 ) and eastern NAO (ENAO 2 ) events, respectively, to unify the NAO 2 and eastern Atlantic-European blocking events into a single NAO 2 system. This leads us to conveniently examine which type of NAO 2 regimes contribute more importantly to extreme cold events over Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Häkkinen et al This process combines, for example, periods when the jet is displaced south of a Greenland block (Scherrer et al 2006;Croci-Maspoli et al 2007;Woollings et al 2008) with periods when the jet is displaced north of an Iberian block (Woollings et al 2011;Davini et al 2012). In this way a period of enhanced blocking in their analysis could correspond to a period of strong intraseasonal variability in jet latitude.…”
Section: Changes In Intraseasonal Variabilitymentioning
confidence: 99%